Dakwah digital Digital Da'wah for Generation Z: Strategies and Challenges in Building Spiritual Awarenes - Febrianto, Mohamad; Muhid, Abdul (Journal International Dakwah and Communication, 2025)
The development of digital technology has created a new landscape in Islamic da'wah activities, especially in reaching Generation Z, known as digital natives. This generation has distinctive characteristics such as high dependence on the internet, preference for visual communication, multitasking, and quick response to concise and instant information. This requires a change in da'wah strategy from a traditional approach to a digital approach that is more interactive, contextual, and participatory. This study aims to analyse effective digital da'wah strategies and evaluate the main challenges in building generation Z's spiritual awareness. The method used was a scoping review based on Arksey and O'Malley's framework, which included literature searches from various scientific databases, article selection, data mapping, and systematic presentation of results. The results show that effective da'wah strategies include the use of a relaxed and popular communication style, the utilisation of attractive visual content that is in line with trends, educational and participatory message delivery, and a consistent and active presence on social media platforms such as TikTok, Instagram, and YouTube. However, digital da'wah also faces serious challenges such as rampant misinformation, low digital literacy among preachers and audiences, Generation Z's spiritual identity crisis, and misuse of digital media for personal gain and popularity.